Health Risks associated with residual pesticide levels in fish reared in purified wastewater from slaughterhouse - PELIĆ, M.; KARTALOVIĆ, B.; ŽIVKOV BALOŠ, M.; MIRILOVIĆ, M.; ĐORĐEVIĆ, M.; TEODOROVIĆ, V.; ĆIRKOVIĆ, M.; LJUBOJEVIĆ PELIĆ, D. (Journal of the Hellenic Veterinary Medical Society, 2020)
The main objective of the present research was to determine the concentrations of the selected pesticides in muscle, liver and skin of common carp. Fish were sampled in two different seasons from fish pond which received previously treated slaughterhouse wastewater. Pesticides including etridiazole, chloroneb, trifluralin, propachlor, chlorothalonil, hexa-chlorocyclopentadiene, atrazine, simazine, alachlor, metribuzin, metolachlor, DCPA, cyanazine, chlorobenzilate, endrin aldehyde, cis permethrin and trans permethrin were determined by using a GS-MS method. Many of pesticides were not determined or determined in low concentrations. Propachlor was found in muscle, skin and liver. The recommended acceptable daily intake was higher in comparison with the estimated daily intake for examined pesticides via fish reared in treated slaughterhouse wastewater. It is very important to maintain the safety of the fresh fish produced in wastewater in order to ensure food safety and avoid health problems in humans.